FACTORS INFLUENCING SMARTPHONE DEPENDENCY BEHAVIOUR AMONG UNIVERSITY STUDENTS - Ima Ilyani Ibrahim; Mohd Fazly Mohd Razali; Mohd Hanif Abdul Wahab; Shamshul Anaz Kassim (International Journal of Accounting, Finance and Business, 2023)
Consumers today are progressively becoming more reliant on their mobile devices. With all of the capabilities and applications available today, mobile phones are used for more than just placing and receiving calls. When a user views their smartphone as a necessity and has a strong connection to the process for more advanced usage, while also being engaged and disciplined to break free from it, the user is exhibiting dependence behaviour. Customers who have used or been heavily associated with smartphones are more likely to not only have first-hand knowledge of their properties or capabilities, but also personal experience with how they function for users and how they satisfy customer needs. This study was carried out to determine the influences on smartphone dependence behaviour among university students in northern Malaysia; including social influence, social requirements, convenience, and perceived ease of use. The researcher will be able to identify the most important component contributing to smartphone reliance behaviour by looking into these factors. A total of 340 respondents from university students participated in this study. The study lasted for six months. The data were analysed using regression analysis and Pearson correlation. The results showed that among university students, social influence, social needs, convenience, and perceived ease of use have an impact on smartphone dependent behaviour.